The training of soccer assistant referees beyond on-field experience: the use of the Interactive Video Test - Armenteros, M.; Benitez, A. J.; Flores, R.; Sillero-Quintana, M.; Cid, M.; Simón, J. A. (International Journal of Computer Science in Sport, 2018)
The main objective of this article was to analyse whether the Interactive Video Test (IVT) is a useful tool for the practical off-field training of soccer assistant referees, and if its use could reduce erroneous on-field decisions when applying Law 11 of the Laws of the Game. Assistant referees were taken from the Spanish 2nd "B" and 3rd Divisions, and were divided into two groups, the Experimental Group (EG) and the Control Group (CG). The referees in the EG were trained with the Interactive Video Test by analysing 720 off-side decisions. Subsequently, both groups were assessed in on-field tests involving the simulation of 326 possible off-side situations. When the results of both groups were compared, there was a continuous improvement over time in the EG associated to the use of the IVT, significantly better than the improvement of the CG. Moreover, the IVT proved to be a good diagnostic tool to assess the skills of assistant referees in perceiving and evaluating off-side situations.